Lotniczy skaning laserowy w polskiej archeologii. Czy w pełni wykorzystywany jest potencjał prospekcyjny metody? - Banaszek, Łukasz (Folia Praehistorica Posnaniensia, 2014)
Airborne Laser Scanning (ALS) is an advanced method of archaeological prospection. One can easily spot an increasing number of applications of LiDAR data within Polish archaeology. Due to that fact it is important to understand the prospective potential of the method as well as subjective character of generated information. The aim of this paper is to describe analytical and interpretative aspects of ALS. Application of LiDAR data is characterised by various processes which lead to the reduction of information about the past. Those processes will be identified and a number of practical solutions aiming to prevent them will be presented. The paper, based on a critical analysis of the procedurę of data acquisition and processing as well as creation of the final products, shows how important is knowledge of subjective character of data, tools and techniques during usage of ALS for archaeological purposes.